2019
DOI: 10.1029/2019gc008512
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Dynamics of the Eastern Mediterranean and Middle East: Constraints From P‐Wave Anisotropic Tomography

Abstract: High‐resolution images of P‐wave anisotropic tomography beneath the Eastern Mediterranean and Middle East are determined by inverting a large number of high‐quality P‐wave arrival times. Our results clearly show along‐strike variations of subducting slabs in the Hellenic subduction zone. At least three high‐velocity anomalies are imaged beneath and behind the north Hellenides, which are associated with the subducting Hellenic slab at different stages, while in regions further south, a single slab is revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 115 publications
(253 reference statements)
11
51
1
Order By: Relevance
“…More recently, Wei et al. (2019) propose a slab tear in the Hellenic slab at 660 km depth, with the rest of the slab imaged to extend beyond 1,000 km depth consistent with Spakman et al. (1993), using P wave anisotropic tomography.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…More recently, Wei et al. (2019) propose a slab tear in the Hellenic slab at 660 km depth, with the rest of the slab imaged to extend beyond 1,000 km depth consistent with Spakman et al. (1993), using P wave anisotropic tomography.…”
Section: Introductionsupporting
confidence: 56%
“…Using receiver functions, Taylor et al (2018) suggested the Cyprean slab penetrates the 660 km discontinuity below the NAFZ. More recently, Wei et al (2019) propose a slab tear in the Hellenic slab at 660 km depth, with the rest of the slab imaged to extend beyond 1,000 km depth consistent with Spakman et al (1993), using P wave anisotropic tomography. Teleseismic tomography studies reveal a fast wave speed anomaly, termed the Bitlis slab, at contrasting depths below Eastern Anatolia: Lei and Zhao (2007) suggest ∼180 km; Zor (2008), Berk Biryol et al (2011), and Portner, Delph, et al, (2018) suggest ∼500-600 km.…”
Section: Previous Geophysical Studiesmentioning
confidence: 97%
“…The delamination of the Eastern Mediterranean ocean floor followed by slab break off and asthenospheric elevation is seen responsible for the uplift of the East and the Central Anatolia (Lei and Zhao 2007;Govers and Fichtner 2016;Feld et al 2017;Çemen and Yılmaz 2017;Kaviani et al 2018;Wei et al 2019;Confal et al 2020), which occurred after the Miocene (Keskin 2003;Cosentino, et al 2012;Schildgen et al 2014). Bartol and Govers (2014) also suggested that the Central Anatolian elevation was related to the westward progression of the East Anatolian lithospheric delamination.…”
Section: Discussion On the Tectonic Development Of The Adana Plain Tmentioning
confidence: 98%
“…Partly coevally with the tectonic events of the northern regions, the slab steepening occurred in the Eastern Mediterranean oceanic lithosphere in the South (Dilek and Flower 2003;Lei and Zhao 2007;Faccenna et al 2013;Govers and Fichtner 2016;Taylor et al 2018;Wei et al 2019;Kounoudis et al 2020;Confal et al 2018). The consequent trench retreat caused a regionwide extension on the upper plate (Robertson 2000).…”
Section: Discussion On the Tectonic Development Of The Adana Plain Tmentioning
confidence: 99%
“…The model shows that the low‐velocity anomaly beneath the Red Sea rift is asymmetrically extending toward the northern regions along the so‐called tectonic equator (Panza et al, 2010). The northward flow of asthenospheric materials from the Red Sea rift was also proposed through investigating the Middle East mantle transition zone using a 3‐D migration of P receiver functions (Kaviani et al, 2018) and a new regional travel time tomography for the Middle East (Wei et al, 2019). Kaviani et al (2018) observed a thin mantle transition zone beneath the Red Sea extending northward beneath the Mesopotamian plain and concluded a hot material flow beneath the plain.…”
Section: Discussionmentioning
confidence: 99%